Molecularly designed, dual-doped mesoporous carbon/SWCNT nanoshields for lithium battery electrode materials. Issue 39 (16th September 2016) - Jang, Ye-Ri; Kim, Ju-Myung; Lee, Jung-Han; Cho, Sung-Ju; Kim, Guntae; Ju, Young-Wan; Yeon, Sun-Hwa; Yoo, JongTae; Lee, Sang-Young
Abstract : An ion/electron-conductive nanoshield based on a SWCNT-embedded, dual-doped mesoporous carbon shell (that was derived from the molecularly designed PVIm[DS]) was presented as an exceptional interfacial control strategy for lithium-ion battery cathode materials. Abstract : Formidable challenges facing lithium-ion rechargeable batteries, which involve performance degradations and safety failures during charge/discharge cycling, mostly arise from electrode–electrolyte interface instability. Here, as a polymeric ionic liquid (PIL)-mediated interfacial control strategy to address this long-standing issue, we demonstrate a new class of molecularly designed, ion/electron-conductive nanoshields based on single-walled carbon nanotube (SWCNT)-embedded, dual-doped mesoporous carbon (referred to as "SMC") shells for electrode materials. The SMC shell is formed on cathode materials through solution deposition of the SWCNT/PIL mixture and subsequent carbonization. The PIL (denoted as "PVIm[DS]") synthesized in this study consists of poly(1-vinyl-3-ethylimidazolium) cations and dodecyl sulfate counter anions, whose molecular structures are rationally designed to achieve the following multiple functions: (i) precursor for the conformal/continuous nanothickness carbon shell, (ii) dual (N and S)-doping source, (iii) porogen for the mesoporous structure, and (iv) SWCNT dispersant. Driven by such chemical/structural uniqueness, the SMC shell prevents direct exposure of cathode materials to bulk liquid electrolytes while facilitating redox reaction kinetics. As a consequence, the SMC-coated cathode materials enable significant improvements in cell performance and also thermal stability. We envision that the SMC shell can be suggested as a new concept of effective and versatile surface modification strategy for next-generation high-performance electrode materials.